Petri nets and autonomous systems: A case study - Leite, Guilherme Eduardo [UNESP]; Marranghello, Norian [UNESP]; Pereira, Aledir Silveira [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2009)
This work presents the Petri net-based modeling of an autonomous robot's navigation system used for the application of supplies in agriculture. The model was developed theoretically and implemented through the CPNTools software. It simulates the behavior of the robot, capturing environmental characteristics by means of sensors, making appropriate decisions, and forwarding them to the corresponding actuators. By exciting the model using CPNTools it is possible to simulate situations that the robot might undergo, without the need to expose it to real potentially dangerous situations. ©2009 IEEE.
Keywords: Autonomous robot; Autonomous systems; Dangerous situations; Environmental characteristic; Factory automation; Graph theory; Petri nets; Semiconductor quantum dots; Robots